CXCL16/CXCR6 axis arises as a potential peripheral biomarker of early COPD development – results from a pilot study - Marques, Patrice; Bocigas, Irene; Domingo, Elena; Francisco, Vera; Tarrasó, Julia; Piqueras, Laura; Signes-Costa, Jaime; González, Cruz; Sanz, Maria-Jesus (Frontiers in Medicine, 2025)
BackgroundChronic obstructive pulmonary disease (COPD) is mainly caused by long-term exposure to cigarette smoke. Since systemic inflammation is an important component of COPD pathophysiology, its characterization is essential for developing new biomarkers and pharmacological approaches. We have previously reported CXCL16/CXCR6 axis upregulation, a key element of leukocyte trafficking in COPD. Given the paucity of data on early-stage COPD patients (GOLD 1), we investigated CXCL16/CXCR6 axis expression in this population and in individuals at risk for developing COPD.DesignBlood samples were collected from 27 GOLD 1 patients, 27 symptomatic smokers with normal lung function (pre-COPD), and 14 non-smokers. CXCR6 expression was assessed in platelets, leukocytes, and leukocyte-platelet aggregates by flow cytometry. Plasma CXCL16 levels were measured by ELISA and lung function by spirometry.ResultsCXCL16 plasma levels and CXCR6 expression on platelets, classical monocytes, B-cells, and leukocyte-platelet aggregates were higher in GOLD 1 patients than in non-smokers and pre-COPD subjects. While CXCR6 expression was similar between the pre-COPD group and non-smokers, plasma levels of CXCL16 were higher in the former. Finally, CXCL16/CXCR6 axis expression negatively correlated with FEV1/FVC ratio.ConclusionThis pilot study provides the first evidence that the CXCL16/CXCR6 axis is upregulated in early-COPD development. Increased CXCL16 plasma levels in GOLD 1 patients and pre-COPD subjects suggest CXCL16 as a potential peripheral biomarker of early COPD development. Given the importance of the CXCL16/CXCR6 axis in leukocyte trafficking, it may emerge as a druggable target to attenuate lung immune cell infiltration and prevent COPD development and progression.